2015
DOI: 10.1097/olq.0000000000000358
|View full text |Cite
|
Sign up to set email alerts
|

Catching Up or Missing Out? Human Papillomavirus Vaccine Acceptability Among 18- to 26-Year-old Men Who Have Sex With Men in a US National Sample

Abstract: Health care providers need to use routine points of contact with YMSM patients to vaccinate against HPV. These data indicated missed opportunities to vaccinate YMSM who are open to HPV vaccination. In the future, HCPs of YMSM should be careful to avoid missed opportunities to vaccinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 28 publications
4
62
1
Order By: Relevance
“…Methods used in this study may be used to assess HPV prevalence and potential vaccine impact in the future, as more men are vaccinated against HPV. Since HPV vaccine was routinely recommended for US males in late 2011, uptake has risen among males, although remaining low overall: in several large surveys of US MSM aged 18–26 years, self-reported HPV vaccine uptake was 4.9% during 2011 [39], 6.8% at the end of 2011 [40], and 13% by 2013 [41]. Increasing vaccination rates suggest that the vaccine impact in this population could be monitored using baseline data from this study.…”
Section: Discussionmentioning
confidence: 99%
“…Methods used in this study may be used to assess HPV prevalence and potential vaccine impact in the future, as more men are vaccinated against HPV. Since HPV vaccine was routinely recommended for US males in late 2011, uptake has risen among males, although remaining low overall: in several large surveys of US MSM aged 18–26 years, self-reported HPV vaccine uptake was 4.9% during 2011 [39], 6.8% at the end of 2011 [40], and 13% by 2013 [41]. Increasing vaccination rates suggest that the vaccine impact in this population could be monitored using baseline data from this study.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2011, coverage for ≥1 dose of HPV vaccine was 6.8% among 1457 MSM using a website for men seeking other men. 9 Among 1098 participants aged 18–26 years in a large online survey for US MSM at-risk for HIV in 2012, 14.0% reported receiving ≥1 dose of HPV vaccine. 10 An online survey conducted in late 2013 found that ≥1 dose coverage was 13.1% among 428 men aged 18–26 years who self-identified as gay or bisexual.…”
Section: Introductionmentioning
confidence: 99%
“…14 Among young MSM (YMSM) aged 18 to 26 years, coverage with 1 or more doses of HPV vaccine was 4.9% in 2011 soon after the national recommendation was issued 15 ; more recent studies of YMSM have identified coverage ranging from 6.8% to 20.8%. 1618 Increasing HPV vaccine coverage is expected to reduce the burden of HPV infections and HPV-associated disease among MSM. 19 …”
mentioning
confidence: 99%